1995
DOI: 10.1037/0033-2909.117.2.250
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of sex differences in spatial abilities: A meta-analysis and consideration of critical variables.

Abstract: In recent years, the magnitude, consistency, and stability across time of cognitive sex differences have been questioned. The present study examined these issues in the context of spatial abilities. A meta-analysis of 286 effect sizes from a variety of spatial ability measures was conducted. Effect sizes were partitioned by the specific test used and by a number of variables related to the experimental procedure in order to achieve homogeneity. Results showed that sex differences are significant in several tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

219
1,767
30
61

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,405 publications
(2,114 citation statements)
references
References 201 publications
(105 reference statements)
219
1,767
30
61
Order By: Relevance
“…Interestingly, the rare allele of rs147546024: A4G was associated with better cognitive performance on blockdesign test which is designed to assess visuospatial ability. Similar to some studies which have described a sex difference in cognitive ability with a male advantage on the spatial domains, 34 our study confirmed slight, but not significant, higher scoring of males on block-design test. It is known that better performance on block-design test is associated with autistic spectrum disorder [35][36][37] and DMD is recognized as one of susceptibility genes for autism disorder.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the rare allele of rs147546024: A4G was associated with better cognitive performance on blockdesign test which is designed to assess visuospatial ability. Similar to some studies which have described a sex difference in cognitive ability with a male advantage on the spatial domains, 34 our study confirmed slight, but not significant, higher scoring of males on block-design test. It is known that better performance on block-design test is associated with autistic spectrum disorder [35][36][37] and DMD is recognized as one of susceptibility genes for autism disorder.…”
Section: Discussionsupporting
confidence: 92%
“…The findings are consistent with previous studies reporting a female advantage in object location memory (e.g., Eals & Silverman, 1994;Hill et al, 1995;James & Kimura, 1997;McBurney et al, 1997;Silverman & Eals, 1992) compared to other forms of spatial cognition where a male advantage is evident (such as mental rotation; Voyer et al, 1995). In contrast to Eals and Silverman (1994) and Silverman and Eals (1992), who employed nonstandardized versions of object memory and object location tests, we demonstrated some support for McBurney et al's (1997) assertion that any female advantage is for recall of spatial locations per se rather than memory for object identity using a standard neuropsychological paradigm.…”
Section: Discussionsupporting
confidence: 92%
“…Typically, males excel on spatial tasks involving mental rotation of three-dimensional figures, spatial visualization (such as mental paper folding), disembedding (finding simple figures hidden in more complex forms), spatial perception (determining horizontal and vertical angles), maze navigation, and targeting and intercepting objects (e.g., Halpern, 1992;Kimura, 1999;Voyer et al, 1995). The origins of these differences are unknown, but has been variably attributed to differences in cerebral lateralization, sociocultural factors and (more recently) the influence of organizational and activational effects of gonadal hormones (Collaer & Hines, 1995;Maccoby & Jacklin, 1974;O'Connor et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, our findings on the Mental Rotations Test extend previous findings with the Rod and Frame Test [19] and a measure of spatial ability composed of the Rod and Frame Test, Hidden Figures, and the Space Relations Test [17]. Our comparatively large effect size of about a standard deviation is not surprising given that the Mental Rotations Test produces one of the larger and more reliable sex differences [52]. Our finding of a significant negative relationship between estrogen and mental rotations contrasts with Hampson's report of an inverted-U function between estrogen and Space Relations scores.…”
Section: Sexually Dimorphic Abilitiessupporting
confidence: 88%
“…We found no significant correlation between mental rotations and FOI priming, suggesting that although both tests vary negatively with estradiol, they tap different abilities. FOI performance may be mediated in part by spatial visualization, a skill that also shows significant sex differences as measured by tests of figural disembedding in which participants identify a simple geometric figure embedded within a more complex pattern [52]. Studies are underway to examine the relationship between spatial visualization and FOI priming.…”
Section: Perceptual Implicit Memorymentioning
confidence: 99%